The Sharklogger Network—monitoring Cayman Islands shark populations through an innovative citizen science program - Johanna Kohler; Mauvis Gore; Rupert Ormond; Timothy Austin; Jeremy Olynik (PLoS ONE, 2025)
The use of citizen science can be a cost-effective tool in conservation science but mostly relies on the collation of incidental sighting reports. This study describes the design, operation, and findings of a novel, closely-guided citizen science program (the ‘Sharklogger Network’) in the Cayman Islands. Participants from the recreational SCUBA diving community used a standardized, effort-based protocol to monitor local coastal shark populations. Over two years (2017–2018) a total of 69 participants conducted 24,442 dives across 472 dives sites and recorded 4,666 shark sightings from eight shark species, of which Caribbean reef shark, nurse shark, and hammerhead spp. were the most frequently observed and encountered throughout the year. The data from dive logs provided evidence for species-specific distribution and abundance patterns across and within islands, indicating a greater abundance of sharks in areas with less anthropogenic activity and with a greater exposure to strong currents, regardless of whether the area was an MPA or not. While both Caribbean reef sharks and nurse sharks showed species-specific depth and habitat preferences, the recording of recognizable individuals showed that some individuals of both species have relatively small home ranges and high site-fidelity to specific areas. The study also provided the first confirmation of reproductive behaviour in both Caribbean reef and nurse sharks taking place in summer (May–August). Experience showed that along with generating valuable data the program, by engaging local stakeholders, also enhanced public awareness of shark conservation issues. This study demonstrates that this citizen science methodology can be an affordable and non-invasive tool for the reliable long-term monitoring of shark populations.